Ragam Modus Cyber Crime Di Era Digital 4.0 - Dede Handayani; Sintia Fardiyanti Rosianah; Dicky Imam Sobari; Dwiansyah Afriandi Putra; Haznissa Muchlis Zulhija; Indah Maulida; Muhammad Arkhab Purnama Agdana; Muhammad Khusni Mubarakh; Wanda Wulansari; Wildan Faizul Khanafi (Abdi Jurnal Publikasi, 2023)
This journal presents the results of a community service program aimed at providing understanding and knowledge about various types of cyber crime in the digital era 4.0 to the students of SMP Al Mubarak. With the increasing use of digital technology in our daily lives, the risk of cyber crime is also on the rise. Thus, it is essential to provide socialization about the most common types of cyber crime in order to minimize such criminal activities. The community service program utilized training and counseling methods to deliver the necessary knowledge and information to the students of SMP Al Mubarak. The counseling was conducted through the delivery of pre-made material, while training was conducted through pre-test and post-test assessments.The results of the program showed that the students still lacked knowledge and understanding about the current types of cyber crime. Most of them did not know how to avoid cyber attacks. Through this program, it is hoped that students will acquire knowledge about various types of cyber crime and how to avoid them. They will also learn about preventive measures that can be taken to reduce the risk of cyber attacks. It is expected that this counseling will help students become more cautious and take better preventive measures to avoid cyber crime. Furthermore, this community service program may have a positive impact on the school environment by encouraging students to become agents of change and reduce the risk of cyber crime in their school.